On an Intervention Regarding Dialectics in Marx and Hegel by Marcos LutzMüller (1982) - Beckenkamp, Joãosinho (Revista Eletrônica Estudos Hegelianos, 2024)
Marcos Lutz Müller, widely known for his translations and commentaries on Hegel, also contributed to a certain renewal of Marx studies in Brazil. This article aims to reconstruct elements of the historical scenario in which his 1982 intervention in the debates on Marx’s dialectics occurred.
Keywords: Dialectics; Hegel; Marx